PENGARUH LATAR BELAKANG PENGETAHUAN PEMBELAJAR TERHADAP PEMAHAMAN TEKS BAHASA INGGRIS - Windy Wahju Purnomo (Metafora: Jurnal Pembelajaran Bahasa Dan Sastra, 2015)
Abstract. This study discussed the impacts of instructional interventions in building, activating, and organizing an EFL adult learner’s background knowledge in comprehending texts. In reading texts, different methods may be applied. Reading scientific texts will be different from reading for leisure or reading news.To understand the content and message of the text, knowledge of language like grammar and vocabularies is not enough. The knowledge of the world or readers’ background knowledge of the topic is the other important aspects in comprehending text. This article is aimed at discussing the importance of instructional interventions in helping readers to build, activate, and organize her prior knowledge on the topic in comprehendingEnglish texts. Therefore the readers can attain comprehension after instructional interventions on building, activating and relating background knowledge are given. Those instructional interventions are given to help the participant build, activate, and organize her background knowledge. Key words: instructional intervention, background knowledge or prior knowledge